A Population Health Approach to Address the Burden of Congenital Heart Disease in Kerala, India. Issue 1 (18th October 2021) - Nair, Sreehari M.; Zheleva, Bistra; Dobrzycka, Adriana; Hesslein, Peter; Sadanandan, Rajeev; Kumar, R. Krishna
Background: Congenital heart disease (CHD) has emerged as a leading contributor to infant mortality in many low-and middle-income countries (LMICs). We report early results of a population health program for CHD, implemented in the state of Kerala, India. Objective: Report on early results of a population-based program implementation in a LMIC to reduce mortality from CHD. Methods: We retrospectively analyzed the results of an innovative population-based program to address CHD. We devised, implemented and evaluated measures in the care continuum to address deficiencies in CHD care in Kerala, India, through structured capacity building initiatives that enabled early detection, prompt stabilization and expedited referral to a tertiary center. A comprehensive web-based application enabled real-time case registration, prioritization of treatment referrals, and tracking every child registered with CHD. Advanced pediatric heart care was delivered through a public-private partnership. Results: Early identification, referral, and treatment of infants with CHD were improved. The web-based application, ' Hridyam, ' registered 502 cases in 2017 (Aug–Dec), 2190 in 2018 and 3259 in 2019; infants < 1 year of age constituted 56, 62 and 63% in these years, respectively. The number of heart operations managed through Hridyam rose from 208 to 624 and 1227 in the same years, with overall 30-day mortality of 2.4%. Overall- and CHD-related infant mortality in Kerala fell by 21.1% and 41.0%, respectively, over the same interval. Unmet challenges include lack of universal catchment and a 5% preoperative mortality rate. Conclusion: We demonstrate successful implementation of a population-based and real-time approach to reduce CHD mortality. We speculate that Hridyam has contributed to the observed decline in Kerala's IMR from 12 to 7 between 2016 and 2019. This model has potential applications for other conditions, and in other jurisdictions, especially LMICs considering building CHD capacity.